INFLUENCE OF SUPERCHISEL BORING SHOCK ABSORBERS DIFFERENT CONSTRUCTIONS ON A VIBROACCELERATION BORING COLUMN - Мойсишин, Василь Михайлович; Смага, Богдан Ігорович; Жовнірук, Роман Андрійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The authors found that the variance of the vibration acceleration of the drilling column and the average power of the process of its change have the same physical content that is they are directly proportional to the values. According to the results of industrial researches it was found that the use of lower cylinder drill diameters of different structures reduces the velocity of vibration acceleration which determines the maximum dynamic load on the elements of the drilling column. At the same time the average power of the fluctuating process of the drilling column is also confused. The influence of different structures of shock absorbers on these values depends on the absorption coefficient of the elastic element of the shock absorber which is determined by the ratio of the area of the hinges loop to the area under the load cell. It is established that the effectiveness of vibration protection (reduction of the amplitude of vibration acceleration of a drill column) increases with increasing this coefficient.